The Importance of Human Capital Efficiency on the Equity Funds Performance during the Covid-19 Pandemic in Indonesia - Christian ADHYASA; Zuliani DALIMUNTHE; Rachmadi Agus TRIONO; Wasilah WASILAH; Shalahuddin HAIKAL (Communications of International Proceedings, 2021)
Investors are willing to pay a management fee for their investment funds if they believe to generate a better return than their investment directly. However, skilled fund managers do not generate without cost. It needs costly research support. This research explored the importance of human capital efficiency on the performance of equity funds during the COVID-19 outbreak in Indonesia. We use six mutual fund performance measurements in this study: Sharpe ratio, Treynor ratio, information ratio, Jensen's alpha, Sortino’s ratio, and Modigliani Miller (MM). Those measurements are the most used in mutual fund performance evaluation. We collected data for 105 equity funds in Indonesia and compared their risk-adjusted performance during the outbreak. Using regression method analysis, we found that human capital efficiency (HCE) positively impacted equity fund performance measurement.  Moreover, we divided all funds into three categories based on the level of HCE: high, medium, and low. We conducted Wilcoxon sign-rank test for each mutual fund category and found that for each category, there were significant differences in cumulative abnormal returns of funds before and during the COVID-19 pandemic in Indonesia.
Keywords: Human Capital Efficiency; COVID-19; Equity Funds; Risk-Adjusted Measurement.